The Effect of the Dakon Game on the Cognitive Function of the Elderly at the Turusgede Rembang PPSLU - Fitria, Nifta Un Mey; Basuki, Hyan Oktodia (Universitas Prima Indonesia, 2026)
Cognitive decline is often considered a natural condition in the elderly. However, this disorder can cause forgetfulness, difficulty concentrating, and communication difficulties, impacting daily activities and quality of life. One non-pharmacological intervention that can be used to improve cognitive function is the traditional game of Dakon. This study aimed to determine the effect of Dakon on the cognitive function of elderly people at the Turusgede Rembang Community Learning Center (PPSLU). The study used a quantitative pre-experimental design with a one-group pre-post test and a cohort approach. The study population consisted of 30 elderly people with cognitive decline, and 28 were selected using a purposive sampling technique. The research instruments included the Mini Mental State Examination (MMSE) questionnaire and the Dakon game standard operating procedures (SOP). Data analysis was performed using the Wilcoxon test with a significance level of α=<0.05. The results showed a ρ value of 0.000<0.05, thus accepting H₁, indicating that Dakon significantly improves cognitive function in the elderly. Most respondents experienced improved cognitive scores due to their ability to follow the game stages well, concentrate, and cooperate during the intervention. One respondent experienced no improvement in cognitive function, influenced by factors such as advanced age, low education level, lack of social interaction, and health conditions such as hypertension. It can be concluded that the traditional Dakon game is an effective non-pharmacological intervention in improving the cognitive function of the elderly at the Turusgede Rembang PPSLU.